A PAF receptor antagonist inhibits acute airway inflammation and late-phase responses but not chronic airway inflammation and hyperresponsiveness in a primate model of asthma. Issue 6 (1992) - Gundel Gundel, R. H. R. H.; Wegner Wegner, C. D. C. D.; Heuer Heuer, H. O. H. O.; Letts Letts, L. G. L. G.
Abstract : We have examined the effects of a PAF receptor antagonist, WEB 2170, on several indices of acute and chronic airway inflammation and associated changes in lung function in a primate model of allergic asthma. A single oral administration WEB 2170 provided dose related inhibition of the release of leukotriene C4 (LTC4 ) and prostaglandin D2 (PGD2 ) recovered and quantified in bronchoalveolar lavage (BAL) fluid obtained during the acute phase response to inhaled antigen. In addition, oral WEB 2170 treatment in dual responder primates blocked the acute influx of neutrophils into the airways as well as the associated late-phase airway obstruction occurring 6 h after antigen inhalation. In contrast, a multiple dosing regime with WEB 2170 (once a day for 7 consecutive days) failed to reduce the chronic airway inflammation (eosinophilic) and associated airway hyperresponsiveness to inhaled methacholine that is characteristic of dual responder monkeys. Thus, we conclude that the generation of PAF following antigen inhalation contributes to the development of lipid mediators, acute airway inflammation and associated late-phase airway obstruction in dual responder primates; however, PAF does not play a significant role in the maintenance of chronic airway inflammation and associated airway hyperresponsiveness in this primate model.